Integrated transcriptomic and proteomic analyses suggest the participation of endogenous protease inhibitors in the regulation of protease gene expression in helicoverpa armigera - Lomate, Purushottam R.; Dewangan, Veena; Mahajan, Neha S.; Kumar, Yashwant; Kulkarni, Abhijeet; Wang, Li; Saxena, Smita; Gupta, Vidya S.; Giri, Ashok P. (Molecular & Cellular Proteomics, 2018)
Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant Capsicum annuum protease inhibitor-7 (CanPI-7) arrests growth and development of Helicoverpa armigera (Lepidoptera: Noctuidae). Using de novo RNA sequencing and proteomic analysis, we examined the response of H. armigera larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supporting a dynamic transition in H. armigera protease expression on CanPI-7 feeding with general down-regulation of protease genes at early time points (0.5 to 6 h) and significant up-regulation of specific trypsin, chymotrypsin and aminopeptidase genes at later time points (12 to 48 h). Further, coexpression of H. armigera endogenous PIs with several digestive protease genes were apparent. In addition to the differential expression of endogenous H. armigera PIs, we also observed a distinct novel isoform of endogenous PI in CanPI-7 fed H. armigera larvae. Based on present and earlier studies, we propose potential mechanism of protease regulation in H. armigera and subsequent adaptation strategy to cope with anti-nutritional components of plants.